Study on the Cytotoxic Microstructure of Titanium Dioxide Nanoparticles by X-Ray Phase-Contrast CT Imaging. (30th July 2022) - Fei, Jingtong; Nie, Shanshan; Zhang, Bo; Teng, Xinli; Chen, Ying; Qu, Yikun; Cheng, Zhuoxin; Guo, Linqi
Abstract : To address the problem of microstructural analysis of titania nanoparticles with high cytotoxicity, the authors propose X-ray phase-comparative CT imaging studies. In this method, the HE-stained section samples were compared with the X-ray phase-contrast CT imaging microscopic images, and 3D texture analysis was used to observe the changes in the preparation of hepatocyte microstructures in the two groups. The results show that X-ray phase-contrast CT imaging microscopic images and their larger image size are closely related to HE staining images, and X-ray phase-contrast CT microscopic images can observe important data of hepatocytes from multiple angles. The ship skeleton extraction method based on the endpoint limit also has advantages over traditional algorithms in extraction accuracy and can provide more 3D feature files, confirming the growth and transformation of normal hepatocytes into hepatocyte cytotoxic microstructures. The distribution effect of using the ensemble process is better than the simple 2D feature set and 3D feature set, and the overall accuracy is improved; the result distribution of the tree determination and random forest methods is also better than that of the support vector machine method. The experimental results show that the X-ray phase-contrast CT images can highlight the 2D and 3D imaging features of the hepatotoxic microstructure of TiO2 nanoparticles and provide data for quantitative analysis.